Atypical placement of totally implantable venous access device in paediatric patients – case reports - Kotowska, Aleksandra; Lewandowska, Zuzanna; Sosnowska, Patrycja; Moryciński, Sebastian; Kmieciak, Katarzyna; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Central line catheterisation plays a crucial role in prolonged treatment in children. Totally implantable venous access devices (TIVADs) are associated with a lower risk of thrombosis and are perceived by patients as more comfortable to use. The catheterisation is most commonly performed through the internal jugular vein or the subclavian vein. The present article shows the cases of two patients in whom atypical placement of a TIVAD was used. The first patient underwent TIVAD placement via femoral vein due to tumour mass in the thoracic cavity and thrombotic stenosis of both jugular and subcostal veins. In the second case, atypical localisation applied to the placement of a reservoir in the left parasternal region. In both patients, the atypical placement of TIVAD resulted in prolonged patency and provided access for further treatment.